Penerapan Prinsip Andragogi Pada Sebuah Pusat Bahasa di Surabaya - Hamida, Sonya Damairia; Setiawan, Jenny Lukito; Wiriana (ANIMA Indonesian Psychological Journal, 2007)
This study aims to look at the application of andragogical principles at an English language institution, including its constraints. Informans were 2 instructors and 2 participants of the institution. Data were collected through interviews and observation. Results reveal that there are several andragogical principles already implemented, such as interactive learning, reward system, and learning through activities. Those which are not yet in accordance with andragogical principles are scarcity of conducting practical and experimental tasks, difference in outcome goals between participants and instructors, lack of coordination in evaluation processes between instructors and the institution, and placing tests not yet running well. Constraining factors are lack of autonomy and learning readyness of the participants, the methods used are not running as good as what was intended, and shortage of time. Recommmendations for the institution, the instructors, as well as the participants to use more effective andragogical principles are discussed. Tujuan penelitian ini adalah mengetahui penerapan prinsip andragogi pada sebuah lembaga pendidikan bahasa Inggris beserta hambatannya. Informan penelitian ini adalah 2 orang pembimbing dan 2 orang peserta didiknya. Metode pengambilan data meliputi wawancara dan observasi. Hasil analisis menunjukkan beberapa prinsip andragogi yang telah diterapkan, yaitu pembelajaran berjalan aktif dan dua arah, digunakannya sistem reward, dan penekanan pembelajaran pada kegiatannya. Hal-hal yang belum sesuai dengan prinsip andragogi meliputi jarangnya pemberian tugas yang bersifat praktis dan eksperimental, adanya perbedaan harapan antara peserta didik dan pembimbing, kurangnya koordinasi dalam proses evaluasi antara pembimbing dan lembaga, dan tes penempatan belum berjalan baik. Kendala yang dihadapi adalah kurangnya kemandirian dan kesiapan belajar peserta didik; metode yang digunakan pembimbing tidak berjalan sesuai dengan harapan semula, dan waktu yang terbatas. Didiskusikan saran bagi lembaga, pembimbing, serta peserta lembaga pendidikan bahasa tersebut guna penerapan prinsip andragogi yang lebih efektif.